Pelatihan Pembelajaran Berbasis Deep Learning pada Guru PAI di MTs Darullughah Wadda’wah Pasuruan - Lutfi Rachman (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2025)
The Deep Learning-based training program at MTSS Darullughah Wadda’wah Pasuruan aimed to enhance the competencies of Islamic subject teachers in addressing 21st-century educational demands. Grounded in the principles of Joyful, Mindful, and Meaningful Learning, the training included socialization, the formation of learning communities, and online mentoring. Teachers were equipped with practical skills to design innovative, collaborative, and contextual lesson plans. The results indicated that the Deep Learning approach significantly improved the quality of teaching and student engagement. The establishment of teacher learning communities also fostered reflection and collaboration. Key topics such as Minimum Competency Assessment (AKM) and the challenges of the Industrial Revolution 4.0 underscored the urgent need for a transformation in the teacher’s role as a learning facilitator. This training is recommended to be extended to more faith-based educational institutions and integrated into continuous professional development programs for teachers.